ISPC Commentary on the Revised proposal for CRP3.5 - September 2012 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
ISPC Commentary on the revised proposal for CRP 3.5: Grain Legumes (revision of August 2012).